Asymmetric transfer hydrogenation–Sonogashira coupling one-pot enantioselective tandem reaction catalysed by Pd(0)–Ru(iii)/diamine-bifunctionalized periodic mesoporous organosilica. Issue 36 (25th April 2017) - Zhao, Yuxi; Jin, Ronghua; Chou, Yajie; Li, Yilong; Lin, Jingrong; Liu, Guohua
Abstract : Pd(0)–Ru(iii )/diamine-functionalized periodic mesoporous organosilica for asymmetric transfer hydrogenation–Sonogashira coupling of iodoacetophenone and arynes is investigated. Abstract : Construction of a bifunctional heterogeneous catalyst through the immobilization of palladium nanoparticles within ethylene-bridged chiral ruthenium/diamine-functionalized periodic mesoporous organosilica is developed. Structural analyses and characterizations show its well-defined chiral single-site ruthenium species, and electron microscopy reveals its ordered mesostructure. As a bifunctional catalyst, it enables an efficient asymmetric transfer hydrogenation–Sonogashira coupling one-pot enantioselective tandem reaction, where Ru-catalysed asymmetric transfer hydrogenation followed by Pd-catalysed Sonogashira coupling affords various chiral conjugated alkynols in high yields with up to 97% enantioselectivity. As presented in this study, uniformly distributed palladium nanoparticles, high ethylene-bridged hydrophobicity, and single-site chiral ruthenium catalytic nature make a synergistic contribution to its catalytic performance. Furthermore, the high stability of palladium nanoparticles within its organosilicate network promotes high recyclability, and it could be used for the asymmetric transfer hydrogenation–Sonogashira coupling one-pot enantioselective tandem reaction of 4-iodoacetophenone and ethynylbenzene at least seven times without loss of its catalytic activity.